2017
DOI: 10.2298/gensr1702435c
|View full text |Cite
|
Sign up to set email alerts
|

Respons of wheat species to irrigation water salinity

Abstract: This study was conducted to investigate the effects of different irrigation water salinity level on chromosomes and shoots of wheat with three different ploidy level (diploid, tetraploid and hexaploid). Greenhouse experiment revealed that irrigation water salinity level had significant effects on shoot dry weight, root dry weight, shoot length and root length (P<0.05). The effects of ploidy level and cultivar shoot dry weight and root dry weight were also found to be significant (P<0.05), but the effects on sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Therefore, seed germination in Petri dishes with saline irrigation water solutions are generally used for rapid identification of plant salt tolerance (Jana & Slinkard 1976). Previous researchers used petri dishes with different NaCl salt solutions in beans (Goertz & Coons 1989;Guvenc & Kantar 1996;Elkoca & Kantar 2003), sorghum (Esechie 1994), bread wheat (Kirtok et al 1994;Coskun & Tas 2017) and different vegetables (Cucci et al 1994) and identified salt tolerant/resistant cultivars in a short time. Citak and Toprak (2016) reported chickpea kernel yield was 351 kg/da at full irrigation and 281 kg/da at deficit irrigation (50%) treatment.…”
Section: Seedling Dry Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, seed germination in Petri dishes with saline irrigation water solutions are generally used for rapid identification of plant salt tolerance (Jana & Slinkard 1976). Previous researchers used petri dishes with different NaCl salt solutions in beans (Goertz & Coons 1989;Guvenc & Kantar 1996;Elkoca & Kantar 2003), sorghum (Esechie 1994), bread wheat (Kirtok et al 1994;Coskun & Tas 2017) and different vegetables (Cucci et al 1994) and identified salt tolerant/resistant cultivars in a short time. Citak and Toprak (2016) reported chickpea kernel yield was 351 kg/da at full irrigation and 281 kg/da at deficit irrigation (50%) treatment.…”
Section: Seedling Dry Weightmentioning
confidence: 99%
“…In this sense, seed germination in saline media in petri dishes is largely used to determine salt resistance rapidly (Jana & Slinkard 1976). Salt tolerance of beans (Goertz & Coons, 1989;Guvenc & Kantar 1996;Elkoca & Kantar 2003), sorghum (Esechie 1994), bread wheat (Kirtok et al 1994;Coskun & Tas 2017) and different vegetables (Cucci et al 1994) were tested in petri dishes with different salt solutions. Germination test results should be proven with small plot and field experiments.…”
Section: Introductionmentioning
confidence: 99%